PREDICTION OF THE THERMODYNAMIC HYDRATE FORMATION CONDITIONS FOR METHANE GAS - Abbasi, A. (Asian Research Publishing Network, 2022)
This research work proposes the analysis of predicted data of hydrate formation conditions in an intelligent optimization-based approach. The thermodynamic conditions for hydrate formation were used to assess the plugging risk. Hydrate formation thermodynamic properties and chemical reaction were statistical analyses on developed model results. Thus, the developed algorithm was applied to the experimental data of gas pipeline to validate the results. This research study improves the present models via a novel approach of an empirical model that predicts and suggests parameters for the thermodynamic hydrate formation conditions of methane gas. Â© 2022. Asian Research Publishing Network (ARPN). All Rights Reserved.